"African Dance Is My Therapy": Perspectives On the Unique Health Benefits of West African Dance. Issue 2 (3rd April 2021) - Conner, Kyaien O.; Patterson-Price, Juanita; Faulkner, Niche
ABSTRACT: Culturally oriented dance has the potential for positive impact on both physical and mental health among professional dancers as well as among dance students in higher education and community dance programs. West African dance in particular has been found to influence a range of health outcomes. Despite available research demonstrating the significant benefits of cultural dance, there is a dearth of research which has examined the self-perceived benefits of cultural dance among dancers themselves. The current project utilized qualitative methodology to examine the psychological and physical health benefits of West African dance from the perspectives of 36 dance students attending a West African dance conference. Findings suggest West African dance can influence positive physical, mental, and social health among dancers and connects them to culture and community in unique and important ways. Implications for research and dance education are discussed.